Artificial intelligence in vocational education and training : understanding learner and teacher perspectives on the integration of generative AI through participatory action research - Chan, Selena [Herausgeber] (Springer, 2025)
"This book details a series of studies across several levels of learning and vocational education and training (VET) discipline areas. In the main, the advent of natural language AI chatbots exampled by ChatGPT, has caused the educational sector to take on a defensive stance. Both schools and the higher education sector are engaged in an on-going ‘arms race’ to prevent learners from using AI to augment assessments. Therefore, there has been a focus on plagiarism prevention, rather than to better understand the potentialities for utilizing AI to support better learning. This book explores the collaborative development and planning between educational developers/learning designers and teachers to design learning activities which could leverage off various artificial intelligence (AI) platforms. In doing, support is provided for effective learning to be undertaken with an emphasis on the learning and application of critical thinking skills. The studies presented through the volume, describe the integration of AI literacy, to support learners in evaluating the relevance and efficacy of AI tools and platforms, and to understand how to best utilize these for specific purposes. This book also synthesizes a framework for the introduction, selection, and implementation of AI into the VET curriculum. It showcases recommendations and guidelines to inform the future integration of AI tools/platforms into the VET curriculum." (Publisher, BIBB-Doku)
E-Book für BIBB-Mitarbeitende über die Bibliothek erhältlich.
Keywords: G 2.2.1 Technologisierung; L Lehren & Lernen; L 1 Curricula & Lehrpläne; I 2.3.5 Australien, Ozeanien; 370; Künstliche Intelligenz; Berufsbildung; Berufsbildungsforschung; Lernen; Digitalkompetenz; Curriculum; Ethik; Aktionsforschung; Neuseeland